2021
DOI: 10.3171/2021.2.focus201085
|View full text |Cite
|
Sign up to set email alerts
|

Interhospital transfer status for spinal metastasis patients in the United States is associated with more severe clinical presentations and higher rates of inpatient complications

Abstract: OBJECTIVE In patients with metastatic spinal disease (MSD), interhospital transfer can potentially impact clinical outcomes as the possible benefits of transferring a patient to a higher level of care must be weighed against the negative effects associated with potential delays in treatment. While the association of clinical outcomes and transfer status has been examined in other specialties, the relationship between transfer status, complications, and risk of mortality in patients with MSD has yet to be explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Of the patients who were admitted emergently, almost half did not undergo surgery during that admission and the cost of the emergent care was significantly higher than the cost of planned admissions. 13 Similarly, de la Garza Ramos et al 15 demonstrated that patients with metastatic spinal disease who were transferred between hospitals had significantly more severe clinical presentations and higher rates of inpatient complications compared to patients directly admitted through clinics. Both studies support the idea that care managed through a multidisciplinary spinal oncology clinic, which coordinates and streamlines care, can provide improved and less costly care for patients and hospital systems.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients who were admitted emergently, almost half did not undergo surgery during that admission and the cost of the emergent care was significantly higher than the cost of planned admissions. 13 Similarly, de la Garza Ramos et al 15 demonstrated that patients with metastatic spinal disease who were transferred between hospitals had significantly more severe clinical presentations and higher rates of inpatient complications compared to patients directly admitted through clinics. Both studies support the idea that care managed through a multidisciplinary spinal oncology clinic, which coordinates and streamlines care, can provide improved and less costly care for patients and hospital systems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that examined interhospital referrals for patients with spinal metastasis stated that some hospitals lack resources and request referrals to specialized centers ( 7 ). Still, the decision to refer the patient to another hospital must outweigh the risks of delay in proper medical treatment ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%